The Nairu, unemployment and the rate of inflation in Brazil - Elcyon Caiado Rocha Lima (Institute for Applied Economic Research (ipea), 2015)
This paper estimates the Brazilian Nairu (Non-Accelerating Inflation Rate of Unemployment) and investigates several empirical questions: the behavior of Nairu along time, error bands for Nairu and the usefulness of Nairu to the conduct of monetary policy in Brazil. There are many recent studies about the Nairu 3/4 Staiger, Stock and Watson (1997), Blanchard and Katz (1997) and Portugal, Madalozzo and Hillbrecht (1999). This article innovates with respect to previous ones because it adopts an econometric model that, in our judgment, is more adequate to deal with the still recent instability of Brazilian economy. We estimate two different state-space models: one with ARCH residuals and another with a Markov- switching regime. The article presents some new evidence on several questions. It shows that the Nairu has been increasing since 1995. It concludes that there is a statistically significant relationship, with correct sign, between deviations of unemployment from the Nairu and inflation. It also shows that the usefulness of the Nairu to the conduct of monetary policy is very limited because its error bands are too wide.
Keywords: 330